2022
DOI: 10.3389/fpsyt.2022.766639
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction and Obstructive Sleep Apnea: A Review

Abstract: Erectile dysfunction (ED) is a disease with a wide scope of etiologies. Obstructive sleep apnea (OSA) is considered one of the risk factors for ED and is less studied. A growing lot of evidence show an association between OSA and ED. This study provides an updated review of the relationship between ED and OSA and the possible physiological mechanisms of ED in patients with OSA based on the current evidence. In clinical interviews, patients with ED may benefit from a sleep evaluation. However, further clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
3
0
1
Order By: Relevance
“…Adverse sleep patterns have significant public health implications. Numerous studies have investigated the correlation between sleep traits, such as insomnia and obstructive sleep apnea (OSA), and the risk of ED [7][8][9]. A large cross-sectional observational study conducted in the Chinese population supports the findings of a Taiwanese population-based cohort study.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Adverse sleep patterns have significant public health implications. Numerous studies have investigated the correlation between sleep traits, such as insomnia and obstructive sleep apnea (OSA), and the risk of ED [7][8][9]. A large cross-sectional observational study conducted in the Chinese population supports the findings of a Taiwanese population-based cohort study.…”
Section: Introductionmentioning
confidence: 79%
“…Some studies have reported that OSA is not associated with ED [34,35]. Another study reported a strong correlation between the severity of OSA and decreased sexual satisfaction, but no significant association with ED [8]. Continuous positive airway pressure (CPAP) and surgical treatments were demonstrated as effective therapies for OSA.…”
Section: Discussionmentioning
confidence: 99%
“…сочетание избыточного веса/ожирения с Аг предполагает наличие эд различной степени тяжести [84]. сочетание эд с ожирением и обструктивным апноэ сна увеличивает риск сердечнососудистых заболеваний и их осложнений [85]. кроме того, существует сильная взаимосвязь между симптомами нижних мочевых путей и эд [86].…”
Section: результатыunclassified
“…In men aged younger than 65 years, only severe OSA is linked with ED; however, for men aged 65 years and older, ED is associated with both moderate and severe OSA ( 102 ). It is important to consider the presence of OSA in men with ED, obesity, and hypertension ( 104 ) and/or symptoms of depression ( 105 ). Treatment with CPAP has been reported to variably have no effect ( 106 ) or improve ( 107-109 ) erectile function, a benefit enhanced by PDE5 inhibitors ( 109 ).…”
Section: Pathophysiology and Associations Of Osa With Other Disordersmentioning
confidence: 99%